2000
DOI: 10.1074/jbc.m003889200
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity in the Highly Heterogeneous M4 Peptidase Family Is Determined by a Small Subset of Amino Acids

Abstract: The members of the M4 peptidase family are involved in processes as diverse as pathogenicity and industrial applications. For the first time a number of M4 family members, also known as thermolysin-like proteases, has been characterized with an identical substrate set and a uniform set of assay conditions. Characterization with peptide substrates as well as high performance liquid chromatography analysis of ␤-casein digests shows that the M4 family is a homogeneous family in terms of catalysis, even though the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 45 publications
1
28
0
1
Order By: Relevance
“…Unlike LL-37, HKH20 is highly resistant to various bacterial proteases (not shown), likely because of the absence of hydrophobic residues in HKH20. Notably, the P. aeruginosa elastase, E. faecalis gelatinase, or the 50-kDa metalloproteinase of P. mirabilis belong to the M4 peptidase family (thermolysin family) and have similar specificities requiring hydrophobic amino acids (Leu, Ile, Phe) at the P1Ј position (48,49). Taken together, from a therapeutical standpoint, our results suggest that strategies based on utilizing endogenous and protease-resistant AMPs with high therapeutic indexes could be highly rewarding.…”
Section: Discussionmentioning
confidence: 75%
“…Unlike LL-37, HKH20 is highly resistant to various bacterial proteases (not shown), likely because of the absence of hydrophobic residues in HKH20. Notably, the P. aeruginosa elastase, E. faecalis gelatinase, or the 50-kDa metalloproteinase of P. mirabilis belong to the M4 peptidase family (thermolysin family) and have similar specificities requiring hydrophobic amino acids (Leu, Ile, Phe) at the P1Ј position (48,49). Taken together, from a therapeutical standpoint, our results suggest that strategies based on utilizing endogenous and protease-resistant AMPs with high therapeutic indexes could be highly rewarding.…”
Section: Discussionmentioning
confidence: 75%
“…Phosphoramidon is a peptide that binds to a specific sequence in the thermolysin active-site region. Sequence differences in this region have been correlated with reduced phosphoramidon sensitivity (13).…”
Section: Discussionmentioning
confidence: 99%
“…ZmpB has a preproenzyme structure that is typical of the M4 family (http://merops.sanger.ac.uk/) of metalloproteases, with conservation of functional regions such as the HExxH active-site motif as well as other conserved amino acids downstream of the active site, including Gxxx ExxxD. De Kreij et al (13) found that there was a great deal of sequence variability among various thermolysin-like proteases but that as long as a small subset of amino acids was conserved (e.g., active site residues and zinc ligands), the group was extremely homogeneous in terms of catalysis. B. cenocepacia ZmpB is inhibited by EDTA and 1,10-phenanthroline, indicating that it is a metalloprotease.…”
Section: Discussionmentioning
confidence: 99%
“…Thermolysin-like proteases that are more phylogenically related to thermolysin are sensitive to phosphoramidon. Phosphoramidon was specifically designed for thermolysin, and sequence differences in thermolysin-like proteases correlate with decreased phosphoramidon sensitivity (11).…”
Section: B Cenocepaciamentioning
confidence: 99%